2022
DOI: 10.7759/cureus.30129
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Importance of Biochemical and Hematological Parameters for Mortality Prediction in COVID-19 Cases

Abstract: The recent coronavirus disease 2019 (COVID-19) pandemic has devastated the world's health and economy and has devastatingly affected social and emotional spheres. Although it was the older population who faced the worst, a good number of the younger population also lost their lives. It was very important to predict who will progress to the worst clinical outcome. Consequently, quick and accurate ways of forecasting mortality in COVID-19 cases are essential to save lives. In this study, 11 predictive parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[16][17][18] It is imperative to determine the severity of MIS-C disease in the early stages to prevent complications, which can be an important cause of mortality and morbidity for children, and to reduce the mortality rate. Previous studies examined NLR, MLR, and SII indices to predict prognosis in adult patients with COVD-19, [19][20][21][22] but these indices were not adequately evaluated in MIS-C patients. This study aimed to evaluate the role of SII, NLR, MLR, and CAR indices in predicting the severity, treatment, and prognosis of MIS-C, and to determine which of these indices among can be the most effective and useful in predicting outcomes.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] It is imperative to determine the severity of MIS-C disease in the early stages to prevent complications, which can be an important cause of mortality and morbidity for children, and to reduce the mortality rate. Previous studies examined NLR, MLR, and SII indices to predict prognosis in adult patients with COVD-19, [19][20][21][22] but these indices were not adequately evaluated in MIS-C patients. This study aimed to evaluate the role of SII, NLR, MLR, and CAR indices in predicting the severity, treatment, and prognosis of MIS-C, and to determine which of these indices among can be the most effective and useful in predicting outcomes.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Coronavirus disease (COVID- 19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has high morbidity and mortality. In April 2020, at the peak of the COVID-19 pandemic, a study reported a hyperinflammatory condition similar to Kawasaki disease (KD) and toxic shock syndrome in pediatric patients in the UK.…”
Section: Introductionmentioning
confidence: 99%